Mediating Role of Self-efficacy in the Link betweenEnvironmental Knowledge and Zero-waste Behavioramong Preservice Elementary Teachers - Yuli Widayanti, Esti; Rosyidiana, Hafidz (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2025)
The researches on the mediating role of slef-efficacy in the correlation between knowledge and zero-wate behavior among elementary pre-service teacher are examined in this study.